Health Risks and Challenges in Earthquake Responders in Nepal: A Qualitative Research. Issue 3 (17th June 2019) - Khatri KC, Jyoti; Fitzgerald, Gerard; Poudyal Chhetri, Meen B.
Abstract: Introduction: While the impact of disasters is strongly felt by those directly affected, they also have significant impact on the mental and physical health of rescue/relief workers and volunteers during the response phase of disaster management. Method: Semi-structured interviews were conducted with 11 experts in the field of disaster management from Nepal, inquiring specifically about the impact of the 2015 mega-earthquake on the mental and physical health of rescue/relief workers and volunteers. A thematic approach was used to analyze the results. These were used to assess the applicability of a previously developed conceptual framework which illustrates the hazards and risk factors affecting disaster response workers and the related hazard mitigation approaches. Results: The findings suggested a relationship between the type of injuries to responders and the type of disaster, type of responder, and vulnerability of location. The conceptual framework derived from literature was verified for its applicability with a slight revision on analysis of experts' opinion based on particular context and disaster setting. Technical skills of responders, social stigma, governance, and the socio-economic status of the affected nation were identified as critical influencing factors to heath injuries and could be minimized utilizing some specific or collective measures targeted at the aforementioned variables. Some geographic and weather-specific risks may be challenging to overcome. Conclusion: To prevent or minimize the hazards for disaster relief workers, it is vital to understand the variables that contribute to injuries. Risk minimization strategies should address these critical factors.